La responsabilidad social y su impacto en la estructura financiera - económica de la empresa Cementos Pacasmayo S.A.A. para contribuir a su desarrollo sostenible - Ballena Vargas, Kristell Elvira (2016)
This research paper pursues objective: To determine the impact of Social Responsibility in Financial Position - Economic Company Cementos Pacasmayo SAA contribute to sustainable development. Whereas social responsibility is one of the main innovations in the achievement of objectives and goals of companies by providing multiple benefits to all its stakeholders. The theme of social responsibility in business, which has not yet been assimilated with sufficient seriousness it deserves, because its philosophy and how they have been treated, tends to be at odds with business interests, which are without question some produce profits, ie the business to be a profitable exercise, as "social responsibility, TURNS OUT TO BE A PROFITABLE BUSINESS", put another way, the actions and decisions with social responsibility are not an expense, is an investment It is generating earnings and profits, in some cases immediately, and other medium and long term. It is unlikely that a company assumes a policy of social responsibility if it becomes an expense that goes against their interests and financial statements, as we can not ignore that in the business language everything is measured in investment costs and recovery Of the same. In that sense by the results determined in Chapter III Results It shows that the company Cementos Pacasmayo SAA makes a good management of Corporate Social Responsibility as a good investment is managed by the Central Management of Social Responsibility of Cementos Pacasmayo by Mr. Carlos Alzamora Paul Cateriano; directly contribute to the sustainable development of the organization and with national and international recognition of local, regional. For the above and according to the results in meeting the objectives: general and specific objectives of this research, in recognition of the discussion can be noted that the company Cementos Pacasmayo SAA comply excellently with organizational modern themes, functional , strategic planning and Environmental Management, Competition Management, Corporate Social Responsibility, Management Good Corporate Governance, with which it maintains continuous and efficient sustainable development for itself, for all stakeholders and their environment.